Contemporary Approach to Brand Consciousness and Development among Selected Garment Manufacturing Industries in Kumasi Metropolis, Ghana: Evidence from a Developing Country. - Boadu , Priscilla Kyei; Akporyo , Beauty Awusi Nyavor (Journal of Marketing Studies, 2023)
Purpose: Brand development is widely available and extensively used by various garment manufacturers. Many garment manufacturers spent a lot of money on brand development to enable their manufactured products to survive in the garment industry. This study, therefore, employed the Akers Model (2012), to explore to brand consciousness and development among Small and Medium Scale garment manufacturers in the Kumasi Metropolis. Methodology: The study employed a case study research design using a focus group discussion as a data collection tool. Data was analyzed using thematic content analyses technique to arrive at the findings. Findings: The results suggest that the small-scale garment manufacturers were conscious of their brands; hence, leveraged the advantage of social media to create awareness of their brands. Their brands represented, quality works, neat work, creativity, trustworthy unique, and stylish among others. The public knows their brands on their social media handles. Almost all of them leveraged the emergence of the COVID-19 last year to distribute nose masks to their communities as a way of brand development. Also, the garment manufacturers used logos to depict their identity, represented on social media, participated in fashion shows, and used mannequins. However, few of them had slogans, customized packaging bags, TV/Radio advertisements, and costumed celebrities with no websites. Some of the challenges they faced include financial challenges, inadequate trainees and no government support. Unique Contribution to Theory, Policy and Practice: The study recommends that the small-scale garment manufacturers should invest in continuous brand development strategies by implementing new generational abilities to inculcate new branding technologies to enable them survive in the global competitive environment.